Student’s communication privacy management on Facebook - Yayu Sriwartini (Jurnal Komunikasi Profesional, 2022)
The purpose of this study was to describe the management of communication privacy of Facebook users. The research used the Theory of Communication Privacy Management . The research approach was quantitative with a survey method. Data collection was carried out using questionnaires distributed online via google.doc from 9-16 March 2020 to around 304 samples of Students of Universitas National who were active users of Facebook. The data were presented in a frequency distribution table and analysed by descriptive statistics. The result shows (1) most respondents were selective in publishing their personal data on Facebook. Only date of birth and religion were considered non- privacy; (2) In conveying certain information or messages through various features on Facebook, most of the respondents applied collective limitation, but still controlled the boundaries. It meant allowing others to view or read various posts, but limiting the active activities of others on their timeline; (3) female respondents expanded access restrictions more for others when they posted feelings of pleasure, happiness, upset, anger and satire. The development of access to privacy is caused by psychological factors and respondents' motivation. Overall, the results of the study indicate that there was a communication privacy management activity of respondents on their Facebook.